2019
DOI: 10.1080/1828051x.2019.1661803
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative indices as metabolic stress predictors in periparturient dairy cows

Abstract: The aim of the study was to determine changes in reactive oxygen species (ROS), serum antioxidant capacity (SAC) and oxidative stress index (OSi; ROS/SAC) from dry off to 30 days postpartum in dairy cows. Furthermore, the relationship between indices of oxidative status (ROS, SAC, OSi) and indices related to metabolic disorders (blood free fatty acids, FFA and b-hydroxybutyrate, BHB) and a-tocopherol (a-T) was determined. Blood samples were collected from 131 dairy cows belonging to four commercial farms, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recently, Invernizzi et al . (2019) observed significant differences in d-ROMs and OSi parameters across the periparturient period, meaning that they may be considered useful biomarkers for oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Invernizzi et al . (2019) observed significant differences in d-ROMs and OSi parameters across the periparturient period, meaning that they may be considered useful biomarkers for oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…According to Durgut et al (2016) in cattle with abomasum displacement, they found that OSI level was significantly greater in cattle with right displacement compared to with left displacement and healthy cattle. Invernizzi et al (2019) found in a study they conducted that the OSI level at the calving time was higher than the dry period and the 30th day after calving. Durgut et al (2013) did not find any difference between the OSI levels of bovine herpes virus-1 infected cattle and healthy cattle.…”
Section: Parametersmentioning
confidence: 92%
“…They stated that the effect of genetic, nutritional, and management strategies on periparturient cow wellbeing cannot be assessed without appropriate tools for measuring metabolic health at both the individual and herd levels especially measuring these parameters from plasma and milk that have strong associations with economically important outcomes related to metabolic health in early lactation, such as disease occurrence, milk yield, and reproductive performance. Furthermore, markers of oxidative status can predict the cow stress and support nutritional choices (Invernizzi et al 2019). Oxidative stress must be monitored separately since often it has no clear relationships with plasma NEFA or BHB, suggesting that inflammatory status can be altered without direct associations with indicators of energy metabolism (Overton et al 2017).…”
Section: How To Feed 20t Cowsmentioning
confidence: 99%